Prophylactic use of antiemetics for prevention of opioid-induced nausea and vomiting: a survey about Italian physicians' practice. - Giusti, Raffaele; Mazzotta, Marco; Filetti, Marco; Daniele, Gennaro; Tsukuura, Hiroaki; Ficorella, Corrado; Porzio, Giampiero; Marchetti, Paolo; Verna, Lucilla (Supportive Care in Cancer, 2019)
Purpose: Antiemetics are being used both for the treatment and prophylaxis of opioid-induced nausea and vomiting (OINV) in clinical practice, despite the lack of evidence for the prophylactic benefit. Studies among Japanese physicians demonstrated over 80% prescribe antiemetics, with neuroleptic antipsychotics as the most commonly prescribed drugs. Our objective was to elucidate the current scenario of the prophylactic use of antiemetics for OINV among Italian physicians.Methods: We conducted a web-based cross-sectional national survey. All the invited participants received an e-mail with an 11-item electronic questionnaire accessible through a direct link. Anonymity was guaranteed. According to the exploratory intent of the survey, we did not predefine any formal statistical hypothesis. Associations between variables were tested by the Pearson chi-square or the Fisher exact test.Results: From January to March 2017, 112 completed the electronic questionnaire (112/256, overall response rate, 43.7%). Nearly half of the participants were oncologists (54; 48.2%). Sixty-one (54.4%) physicians worked in palliative care units. About 45% of the interviewed prescribed prophylactic antiemetics at the beginning of opioid prescription. The most commonly chosen drugs for this purpose were prokinetics such as metoclopramide and domperidone (84%), followed by 5-HT3 antagonists (8%), neuroleptic antipsychotics (6%), and corticosteroids (2%). Ninety-one physicians (81%) declared to prescribe antiemetics at the occurrence of OINV, mainly prokinetics (N = 70; 77%).Conclusion: Italian physicians do not commonly prescribe prophylactic antiemetics for OINV. Unlike previously reported data, dopamine antagonists resulted the most commonly prescribed drugs. Prospective clinical trials are necessary to evaluate the real efficacy of this practice.